Neonatal ECMO study of temperature (NEST): a randomized controlled trial. - Field, D; Juszczak, E; Linsell, L; Azzopardi, D; Cowan, F; Marlow, N; Edwards, D (2013)
BACKGROUND: Despite evidence to support the use of extracorporeal membrane oxygenation (ECMO) in defined groups of newborn infants, rates of impairment among survivors remain high. Therapeutic hypothermia has been shown to provide neuroprotection in mature infants exposed to perinatal asphyxia. We hypothesized that therapeutic hypothermia during ECMO would reduce the proportion of infants with brain injury, and thus later impairment. METHODS: We conducted a randomized trial in the United Kingdom to compare ECMO with cooling (34°C for the first 48 to 72 hours) with standard ECMO (37°C). The primary outcome was the cognitive composite score of the Bayley Scales of Infant and Toddler Development, 3rd edition, at 2 years. Prespecified secondary outcomes included death, neonatal morbidity, and other neurodevelopmental and behavioral outcomes at 2 years. RESULTS: A total of 111 infants were entered into the study, 14 died before 2 years of age (16% who received ECMO with cooling vs 9% who received ECMO alone). Two infants were lost to follow-up, and 8 were unable to complete the full range of tests. For 45 evaluated infants who received ECMO with cooling, mean cognitive scores at 2 years were 88.0 (SD: 16.2) compared with 90.6 (SD: 13.1) for 48 infants receiving ECMO only (difference in means: -2.6; 95% confidence interval: -8.7 to 3.4). The various secondary outcomes were not significantly different between the groups, but most favored ECMO without cooling. CONCLUSIONS: In newborn infants treated by ECMO, the use of mild hypothermia for the first 48 to 72 hours did not result in improved outcomes up to 2 years of age.